From policy to practice : Women come together to speak as one voice - Levy, Moira (New Agenda: SA Journal of Social and Economic Policy, 2024)
The festive event incorporated powerful and poignant culture items from women cultural activists. Poets Diana Ferrus and IFAA board member Bernadette Muthien contributed readings of their own work, and Trudy Rushin and daughter Summer Dawn Geffen opened the proceedings with jazz and song. This event was also a collaboration with the Government Communication and Information Services and Parliament’s Public Education Department who arrived in Parliament’s colourful ‘Democracy Bus’. Some of the key organisations present included the Heinrich Böll Stiftung, Ubuntu Rural Women and Youth, and the South African Women’s Law Association.